2019
DOI: 10.1155/2019/8560527
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Cuphea aequipetala Extracts on Murine B16F10 Melanoma In Vitro and In Vivo

Abstract: Cuphea aequipetala (C. aequipetala) has been used in Mexican traditional medicine since prehispanic times to treat tumors. In this paper, we evaluated the antiproliferative and apoptotic effect of the methanolic and aqueous extracts of C. aequipetala on several cancer cell lines including the B16F10 cell line of murine melanoma and carried a murine model assay. In vitro assay analyzed the effect in the cellular cycle and several indicators of apoptosis, such as the caspase-3 activity, DNA fragmentation, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Alcohols: methanol showed a cytotoxic and antiproliferative effect in MCF-7, HepG2 and B16F10 cell lines [ 61 ]. Ethanol exposure suppresses mitochondrial dynamics and sensitizes mitochondrial permeability transition pore opening to promote cell death [ 62 ].…”
Section: Methods Applied For Permeabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohols: methanol showed a cytotoxic and antiproliferative effect in MCF-7, HepG2 and B16F10 cell lines [ 61 ]. Ethanol exposure suppresses mitochondrial dynamics and sensitizes mitochondrial permeability transition pore opening to promote cell death [ 62 ].…”
Section: Methods Applied For Permeabilizationmentioning
confidence: 99%
“…Non-ionic detergents served to permeabilize plasma membrane [ 61 , 62 , 63 ]. The optimization of other commonly used permeabilizing agents included the use of different saponin preparations, digitonin and recombinant lysing solutions such as perfringolysin O [ 64 ].…”
Section: Methods Applied For Permeabilizationmentioning
confidence: 99%
“…Antiproliferative and apoptotic activities of methanolic and aqueous extracts of C. aequipetala have been reported for several cancer cell lines: B16F10, HepG2, and MCF-7 [ 128 ]. The methanolic extract induced cell accumulation in G1 phase, DNA fragmentation, and increased caspase-3 activity in B16F10 cells in vitro.…”
Section: Pharmacological Activity Of Cuphea Plants...mentioning
confidence: 99%
“…Rajasekar et al [ 24 ] showed the anticancerous effect of Lithospermum erythrorhizon extract in vitro and in vivo . Uscanga-Palomeque et al [ 25 ] showed the inhibitory effect of Cuphea aequipetala extracts on melanomas in vitro and in vivo . In coherence with these findings, a keen interest in a Cameroonian pharmacopoeia plant called Piper capense from the Piperaceae family was taken into consideration due to its therapeutic virtues, most especially in the treatment of several illnesses like cancer when used in the form of formulation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%